Robust Control and Optimization Method for Single-Phase Grid-Connected Inverters Based on All-Pass-Filter Phase-Locked Loop in Weak Grid - Longyue Yang; Tian Cao; Huapeng Chen; Xinwei Dong; Shuyuan Zhang (Energies, 2022)
In a distributed generation system, the all-pass-filter phase-locked loop (APF-PLL) is a commonly used method for grid synchronization. However, the coupling effect between APF-PLL and current control loop increases the risk of oscillation instability for the inverter in the weak grid. At present, there are few effective methods to solve the adverse effect of APF-PLL on the inverter-grid interconnection system in the weak grid. Therefore, a small-signal impedance model of the inverter considering the dual d-q frame brought by APF-PLL is first established. Then the reason for the inverter instability caused by APF-PLL in the weak grid is analyzed. Subsequently, an impedance reshaping method based on a modified first-order filter PLL with a complex coefficient filter (CCF-MFOF-PLL) and its parameter optimization design method are proposed. Finally, the experimental results verify that the proposed method widens the stable range of the inverter and ensures the stable operation of the inverter even with the large grid impedance.